2016
DOI: 10.1158/1055-9965.epi-15-0907
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillectomy and Incidence of Oropharyngeal Cancers

Abstract: Background: Rising incidence of oropharyngeal cancers in numerous countries since the 1970s has been attributed to increased oral human papillomavirus (HPV) exposure. However, the contribution of coincidental declines in the surgical removal of the tonsils (tonsillectomy) is unknown. We quantified the association of tonsillectomy with risk of tonsillar, other oropharyngeal, and other head and neck cancers and the contribution of declines in tonsillectomies to cancer incidence trends.Methods: We conducted a nat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 29 publications
3
26
2
1
Order By: Relevance
“…44,45 While tonsillectomy was associated with decreased odds of tonsillar cancer, increased odds of cancer of the base of the tongue were reported. For example, in women with cervical precancer, excision of the cervical transformation zone nearly eliminates risk of progression to cervical cancer.…”
Section: Treatment Of Early (Nonsymptomatic) Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 While tonsillectomy was associated with decreased odds of tonsillar cancer, increased odds of cancer of the base of the tongue were reported. For example, in women with cervical precancer, excision of the cervical transformation zone nearly eliminates risk of progression to cervical cancer.…”
Section: Treatment Of Early (Nonsymptomatic) Lesionsmentioning
confidence: 99%
“…Indeed, retrospective data have suggested that tonsillectomy (removal of the relevant lymphoid tissue and associated epithelium) reduces the risk of OPC. 44,45 While tonsillectomy was associated with decreased odds of tonsillar cancer, increased odds of cancer of the base of the tongue were reported. 46 In addition, tonsillectomy has its own inherent risks (life-threatening or catastrophic bleeding), and therefore optimizing the ability to predict the patient's risk of developing HPVdriven OPC becomes paramount, as does demonstrating that the benefits outweigh the harms (including considerations of quality of life and cost-effectiveness).…”
Section: Treatment Of Early (Nonsymptomatic) Lesionsmentioning
confidence: 99%
“…Studies looking at the Swedish and Danish cancer registries found that tonsillectomy significantly reduced the risk of developing tonsillar carcinoma. 41,42 A more recent study looking at the North Carolina Central Cancer Registry examined the effect of prior tonsillectomy on the incidence of oropharyngealc arcinomaby subsite. 43 This group found that tonsillectomy was associated with a two-fold increase in the risk of base-of-tongue carcinoma (odds ratio, 1.95; 95% CI, 1.25 to 3.06; P = .003), particularly when tonsillectomy was performed at a young age.…”
Section: Surgery As Preventionmentioning
confidence: 99%
“…A nation‐wide study from Sweden (1970‐2009) observed that tonsillectomies (N = 225 718) were associated with reduced risk of tonsil cancers (standardized incidence ratios [SIRs] 1+ years post‐tonsillectomy = 0.31; 95% CI = 0.08‐0.79 and 5+ years post‐tonsillectomy = 0.17; 95% CI = 0.02‐0.62), but unrelated to other oropharyngeal or other head and neck cancers (SIRs 1+ years post‐tonsillectomy = 1.61; 95% CI = 0.77‐2.95 and 0.92; 95% CI = 0.64‐1.27, respectively) . The authors did not believe tonsillectomies should be considered as a secondary prevention strategy for tonsil cancers or other oropharyngeal cancers at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reasons were that: tonsillectomies did not alter risk of non‐tonsil oropharyngeal cancers, and the mortality due to tonsillectomy outnumbers the incidence of oropharynx cancers. Other obstacles were inadequate risk stratification for the identification of high‐risk individuals, inadequate identification and location of premalignant lesions, and lack of low‐morbidity, cost‐effective treatments for premalignant lesions …”
Section: Discussionmentioning
confidence: 99%